Tailoring the Optical Parameters of Optical Fiber Interferometer With Dedicated Boron‐Doped Nanocrystalline Diamond Thin Film. Issue 11 (4th October 2017) - Majchrowicz, Daria; Kosowska, Monika; Struk, Przemysław; Jędrzejewska‐Szczerska, Małgorzata
Abstract : An optical fiber interferometer using nanocrystalline boron‐doped diamond film is investigated. The diamond films are deposited on glass plates using a Microwave Plasma‐Enhanced Chemical Vapor Deposition (µPE CVD) system. The growth time is 3 h, with boron doping level of 10 000 ppm producing films (B‐NCD‐10) of thickness ≈200 nm. The presence of boron atoms in the diamond film is evident in Raman spectrum as peaks at 1212 and 1306 cm −1 . The scanning electron microscopy (SEM) images show homogenous and continuous surface morphology, thus enabling the use of the diamond film as a reflective layer in fiber optic devices. The optical fiber interferometric sensor in Fabry‐Pérot configuration with a diamond reflective layer as a mirror was designed and built. Measurements are performed using two superluminescent diodes with central wavelengths of 1290 and 1550 nm. The detection of the measured signal is achieved using an optical spectrum analyzer. All devices are connected with commercially available, single‐mode telecommunications fibers and coupler. Using B‐NCD‐10 films in fiber optic interferometer a very high value of the measured signal contrast is obtained, equal to 0.99. The use of B‐NCD‐10 film as a reflective surface allows the Fabry‐Pérot cavity length to be reduced while achieving very good signal visibility. Consequently, the volume of the sample in the cavity can be reduced, compared with that of the traditional mirrors. Abstract : An optical fiber interferometer in Fabry‐Pérot configuration with a boron‐doped diamond reflective layer as a mirror was developed. The quality of the layer was examined by scanning electron microscopy (SEM), atomic force microscopy (AFM) and Raman spectroscopy–the results showed that the surface is homogenous and continuous and boron doping process was successfully performed. The use of boron‐doped diamond layer provided a very high value of signal visibility, reduction of the required sample's volume and the possibility of measuring aggressive substances.